Kontribusi Tuan Guru Sapat Dalam Perkembangan Pendidikan Islam Di Indragiri Riau 1908-1939 - Muthalib, A.; Indra Putra, Edi Susrianto; Khairuddin, Khairuddin (Tadarus Tarbawy : Jurnal Kajian Islam dan Pendidikan, 2024)
Islamic Religion has been present and developed in the *Onderafdeeling* Indragiri Riau region for several centuries through neighboring areas. However, the actual practice of Islam in Indragiri Riau was not fully aligned with the teachings brought by Prophet Muhammad SAW. Nevertheless, Islamic teachings underwent significant *changes* in the early 20th century when Tuan Guru Sapat (Syekh Abdurrahman Shiddiq) settled in the area. Therefore, this research aims to explore in detail the contributions of Tuan Guru Sapat during his relatively brief presence in the region, which nonetheless had significant implications for the Riau community, particularly in the Indragiri Hilir area. This study employs historical research methodology, including: *Heuristic* (data collection process), verification (source criticism), interpretation (data analysis), and *historiography* (historical writing process). The research findings reveal several key contributions by Tuan Guru Sapat in the region: 1. Establishment of the first Islamic boarding school in Indragiri Hilir Riau 2. Appointment as Mufti in the Indragiri Riau Kingdom 3. Encouragement of Indragiri residents to pursue studies abroad (Mecca, Medina, Egypt, etc.) 4. Promotion of more serious agricultural practices among Indragiri Riau residents. Keywords: Tuan Guru Sapat's Contribution